Influence of Tides Level on Tsunami Hydrodynamic in Banda Aceh, Indonesia - Tursina, Tursina; Syamsidik, Syamsidik; Kato, Shigeru; Afifuddin, Mochammad (International Journal of Disaster Management, 2023)
Tides are the dominant physical process in the coastal environment. During high tide, water from the ocean flows through the bays and estuaries, causing inundation and raising water elevation. When low tides condition, the water level becomes lower than average and recedes into the sea. This process continues for a long day. Tsunami waves will interact with all coastal processes and affect the hydrodynamic forces of tsunami waves. In the deep sea, tides do not significantly influence wave propagation. However, in the shallow water zone, tides can change tsunami heights and affect the extent of inundation. Tides are usually ignored in tsunami hazard analysis. This would be an underestimate of the tsunami hazard calculation. This study aims to investigate tides' influence on tsunami runup hydrodynamics in Banda Aceh. The potential tsunami from an earthquake in the Aceh-Andaman subduction zone is modeled using COMCOT (Cornell Multi Grid Coupled Tsunami Model) with magnitudes Mw 9.2, 8.6, and 8.2. We simulated the response of the three earthquake magnitudes on two different types of high and low tides. Several virtual gauges were placed to observe the tsunami height. Virtual gauges were also used to observe the tsunami arrival time at four tsunami escape buildings in Banda Aceh: the Ulee Lheue escape building, the Deah Glumpang escape building, the Alue Deah Teungoh escape building, and the Lambung escape building. The results show that the highest tide amplifies the tsunami inundation will be extended to about 30% farther inland compared to the condition if the tsunami occur during mean sea level condition.The interactions between tsunami and high tide significantly shorten tsunami arrival time on small magnitude tsunamis and are not significant in a large tsunami. This information is useful for enhancing early warning systems and evacuation procedures that can be adjusted to the tidal conditions in the study area.